Fairness analysis of e-commerce protocols based on strand spaces. (1st January 2013) - Liu, Yichun
Strand space logic is a formal method for analysing the security protocol. The electronic commerce protocols are of more complex structures, for example, branch structures, or a protocol is composite of multiple sub-protocols, so the analysis of electronic commerce protocols is far more complex than the analysis of authentication protocols. Fairness is a very important feature in e-commerce protocol. But traditional belief logic is not suitable for this. In this paper, we analyse the strand and bundle of ISI payment protocol and then prove its unfairness. We also present a strand node path method to analyse ASW protocol, which consists of multiple sub-protocols with branch structure, and the strand space analysis shows that this protocol is fair.